Revitalisasi Pendidikan Karakter di Paud Terpadu Aisyiah Nur’aini Yogyakarta - Nadlifah, Nadlifah (Al-Athfal: Jurnal Pendidikan Anak, 2015)
This study aimed to know the Revitalization character education in integrated early childhood Aisyiyah Nur’aini Yogykarta. The research approach was used in this study is a qualitative approach. the research Subjects were headmaster, teachers and students. The research data was collected using interviews, observation, and documentation. Based on this study it was found that the revitalization of characters education in Integrated early childhood 'Aisyiyah Nur'aini through the preparation of SOP (Standard Operating Procedure) for the entire school community to implement consistently and commitment. cultivation of the character value is given through the example, habituation and repetition in daily life. In supporting the revitalization of character education, the school held the parenting education and parent class.